Process Optimization Method for Reducing the Thickness Difference of Cathode Foil for Power Batteries - Zuo, Xiaogang; Lv, Zhimin (Metals (Basel ), 2024)
The rolling process of aluminum foil is subject to the issue of variable thickness, which has a substantial impact on its performance. The thickness of the aluminum foil is influenced by various factors, including the magnitude of the bending force, the distance between the rollers, the thermal expansion of the roller, and the acceleration of the rolling mill. To address the issue of quick fluctuations in bending force during the rolling process, either a positive bending force or a slight negative bending force is employed. The adjustment factor for the bending force applied to the roll gap is set to a value of 1.0. Upon conducting a comparative analysis of the thermal expansion curves of the model with varying thermal expansion coefficients, it was ascertained that an optimized coefficient of 1.71 yielded the most favorable results. The roll gap is adjusted using a sixth power equation to accommodate the rolling of materials with both low and high pressure. Subsequently, the roll is elevated by 0.2 mm and 0.18 mm for the entire duration. The findings from the rolling experiments indicate that the optimization of the process leads to a notable reduction in the variance of aluminum foil thickness.